World History - A Genealogy Private Conversations with World Historians, 1996-2016 - Schrikker, Alicia; Stolte, Carolien (Leiden University Press, 2017)
This volume charts the history of the discipline through twenty-five in-depth conversations with historians whose work has shaped the field of world history in fundamental ways. These conversations, which took place over a period of twenty years for the world history journal Itinerario, cover these historians' lives, work, and views of the academy in general and the field of world history in particular. An extensive introduction distills the most important developments in the field from these conversations, and sheds light on what these historians have in common, as well as - perhaps more importantly - what separates them.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: History / World; History; Electronic books